Pancreatic Enzyme Replacement Therapy for Patients Diagnosed With Pancreaticobiliary Cancer: Validation of an Algorithm for Dose Escalation and Management. Issue 9 (3rd October 2021) - Carnie, Lindsay E.; Farrell, Kelly; Barratt, Natalie; Abraham, Marc; Gillespie, Loraine; Satyadas, Thomas; McNamara, Mairéad G.; Hubner, Richard A.; Geraghty, Joe; Bibby, Neil; Valle, Juan W.; Lamarca, Angela
Abstract : Objective: An algorithm was designed aiming to provide consistency of pancreatic enzyme replacement therapy (PERT) dosing/titration across healthcare professionals in pancreaticobiliary cancers (PBCs). This prospective observational study aimed to validate this algorithm. Methods: Consecutive patients with inoperable or postoperative PBC with pancreatic exocrine insufficiency (PEI) symptoms, not taking PERT, or taking below the algorithm "starting dose, " were eligible. A dietitian or clinical nurse specialist reviewed patients for up to 3 weeks, titrating PERT as per the algorithm. Feasibility of algorithm deliverability was assessed by the percentage of patients with successful completion (primary objective). Results: Twenty-five patients were eligible (N = 25): at baseline, 22 took PERT (100% on suboptimal doses, 54.5% taking incorrectly) and 3 initiated PERT because of PEI symptoms. Algorithm completion (20 of 25, 80%) confirming deliverability by dietitians (11 of 12, 92%) and clinical nurse specialists (9 of 13, 69%). Symptom resolution occurred in 8 of 19 (42%), 3 of 7 (43%), and 1 of 3 (33%) patients at first, second, and third reviews, respectively; advice compliance was between 63% and 86%. Conclusions: This algorithm provides a structured method to titrate PERT. At diagnosis, all patients with PBC should be assessed for PEI and adequate PERT initiated. Regular reviews are required for timely symptom resolution and adequate escalation, facilitating differential diagnosis if refractory symptoms exist.